Evaluasi Hasil Individu Program Bootcamp Digital Ruangguru 2018-2019 di PKBM Intan Bandung - Rabia Edra Almira; Ety Rahayu (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
Abstract: The low participation rate below the national average for high school (SMA) students inBandung City in 2018-2019 has prompted the Ruangguru Foundation and PKBM INTAN to provide the Ruangguru Digital Bootcamp Package C program. This research aims to individually evaluate the outcomes of the program, which has carried out a set of activities related to academic education and soft skills. The program proposes to create independent and empowered individuals in order to reduce youth unemployment. Using a qualitative approach, this type of evaluative research describes the outcomes achieved based on the indicators specified by the program implementers. The evaluation is also based on the concept of empowerment in the realm of social welfare related to out- of-school students. The research was conducted in-depth to a sample of beneficiaries who have the goal of working or pursuing higher education after completing all stages of the program. Through interviews and documentation studies, the research results show that the indicators of program success in the outcome aspect have been achieved, namely having a sense of self-confidence and increasing their intellectual capacity or soft skills.